Faktor-faktor yang mempengaruhi kinerja karyawan Bank Syariah Indonesia - Rofiliana, Lugas; Rofiuddin, Mohammad (Nur Science Institute, 2021)
The purpose of this research is to determine the influence of leadership, work environment, Islamic work ethics, and job satisfaction on employee performance of BSI KC Semarang. The sample used in this study was 43 employees with the sampling technique using surfeited sampling, which made the entire population a sample. Retrieval of data through the distribution of structured questionnaires. The analytical method used is multiple linear regression. The results showed that the variables of leadership and work environment were positive towards employee performance. Meanwhile, Islamic work ethics and job satisfaction have no effect on employee performance.